2021
DOI: 10.1029/2021ea001879
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the Koma Bangou Gold Panning Site (Niger) From 1984 to 2020 Using Landsat Imagery

Abstract: Artisanal and small-scale mining (ASM) is mainly prevalent in developing countries (Abaidoo et al., 2019;S. Keita, 2001;Owusu et al., 2019). A few years ago, small-scale mining was estimated to account for 15%-20% of global non-fuel mineral production (Hentschel et al., 2002). Although the African continent is home to some of the world's most coveted mineral resources, this favorable geological context has largely failed to lead it toward an equitable and sustainable development trajectory (Hilson, 2002). In s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 62 publications
0
9
0
Order By: Relevance
“…The shortwave infrared band for Landsat 8-OLI (0.665) shows a strong positive weighting. The strong positive weights are marked by a low value of the Saley et al, 2021;Ghislain et al, 2021;Gomez, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The shortwave infrared band for Landsat 8-OLI (0.665) shows a strong positive weighting. The strong positive weights are marked by a low value of the Saley et al, 2021;Ghislain et al, 2021;Gomez, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The strong positive weights are marked by a low value of the extraction areas (black pixels), whereas the strong negative weights show a high value of the extraction areas (white pixels). Several previous studies have demonstrated the contribution of the NIR and SWIR 1 band in lithologic mapping through the absorption and reflectance of rock materials in the NIR‐SWIR 1 domain (Abass Saley et al., 2021; Ghislain et al., 2021; Gomez, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations